The process of wage adjustment: An analysis using establishment-level data - Alberto Bayo-Moriones; José Enrique Galdón-Sánchez; Sara Martinez-de-Morentin (Institute for the Study of Labor (IZA), 2011)
This article presents a study of the influences on the factors that shape wage adjustments. The cost of living, comparability with other firms' wages, the fulfilment of collective agreements at sector level, the need to recruit and retain employees, the performance of the organisation, and the climate of industrial relations are included as factors of interest. The analysis was carried out using a sample of Spanish manufacturing plants. Our results show that the structural characteristics of the establishment such as its size or foreign ownership, as well as the wage setting arrangements and trade unions, play a role in explaining the importance of the factors mentioned in shaping wage adjustments. The human resource management policies adopted by the employer seem to be less relevant, although the qualification of workers and the use of pay for performance have a significant impact on the process of wage adjustment.
urn:nbn:de:101:1-201110263363
Keywords: J30; J40; 330; pay settlements; collective bargaining; wage negotiation; Lohn; Anpassung; Lohnverhandlungen; Tarifpolitik; Schätzung; Verarbeitendes Gewerbe; Spanien